2005
DOI: 10.1007/s00262-005-0682-5
|View full text |Cite
|
Sign up to set email alerts
|

CD8 T cells expressing NK associated receptors are increased in melanoma patients and display an effector phenotype

Abstract: CD8+ T cells can express NK-associated receptors (NKRs) that may regulate their cytolytic function. We have characterized the expression of several NKRs on peripheral blood CD8+ T cells from melanoma patients and compared them to age-matched healthy donors. The analysis performed includes HLA class I specific receptors (KIRs, LILRB1 and CD94/NKG2) and other NK receptors like CD57, CD56 and CD16. Melanoma patients showed a higher variability in the expression of NKRs on circulating CD8+ T cells than age-matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 65 publications
5
45
1
Order By: Relevance
“…When the study of NKRs on CD8 T cells was made according to the CD28 coexpression, it could be confirmed that the expression of NKRs, as previously reported (4,15), was more frequent on CD8 + CD28 À T cells than on CD8 + CD28 + T cells, both in patients and in controls.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…When the study of NKRs on CD8 T cells was made according to the CD28 coexpression, it could be confirmed that the expression of NKRs, as previously reported (4,15), was more frequent on CD8 + CD28 À T cells than on CD8 + CD28 + T cells, both in patients and in controls.…”
Section: Resultssupporting
confidence: 77%
“…These changes observed in the CD8 + T-cell population seem to be associated with a favorable prognosis, because they were not detected in lymph node metastatic melanoma patients, where the number of CD8 + CD28 À T cells was close to that of healthy individuals, suggesting that in advanced stages of the disease there is less availability for the activation of CD8 T cells (4). In this sense, our data are in agreement with those reported about the decrease of CD8 + DR + T cells in metastatic patients (12), but they are also able to show that the HLA-DR down-modulation in patients at this stage is specially restricted to the CD8 + CD28…”
Section: Discussionmentioning
confidence: 91%
“…One of the major changes that occurs after chronic T-cell activation and cancerous conditions is the down-regulation of CD28 and expansion of CD8 ϩ CD28 null T cells. 26,[32][33][34][35][36] Consistent with previous findings, CD8 ϩ CD28 null T cells were dramatically overrepresented in the peripheral blood of LGLL patients compared with healthy donors, as shown in Figure 4A,B. The absolute number of CD8 ϩ CD28 null T cells present in the blood was greater in LGLL patients compared with healthy donors and nearly all of the patients' CD8 ϩ T cells lacked CD28 expression.…”
Section: Cd8 ؉ Cd28 Null Phenotype Characterizes Leukemic Lgl Cellssupporting
confidence: 89%
“…ϩ TCR␥␦ ϩ T cells (44), EBV-selected synovial TCR␣␤ ϩ T cell clones derived from rheumatoid arthritis patients (45), and expanded CD8 ϩ CD28 null T cells in melanoma patients (46). In addition, KIR2DS2 has been shown to be expressed by the CD4 ϩ CD28 null T cells that expand in some patients with rheumatoid arthritis (47).…”
Section: Discussionmentioning
confidence: 99%